Akanthoparapseudes alfaroae, a new genus and species of apseudomorphan tanaidacean (Crustacea: Malacostraca: Peracarida) from Puerto Rican coastal waters - Heard, Richard W.; Morales-Núñez, Andrés G. (Zootaxa, 2011)
Akanthoparapseudes alfaroae, n. gen., n. sp., is described from material collected at a depth of 28 m off Culebra Island on the eastern coast of Puerto Rico. The new genus, which is tentatively placed in the family Parapseudidae, is distinguished from other parapseudid genera by a combination of characters, including: (1) pereonites 2 to 6 subquadrate with posterolateral margins each armed with small, but distinct spiniform seta, (2) the first pleonite with anterodorsal margin lacking a distinct transverse row of small setulate setae, (3) maxilliped palp having distolateral margin of article 2 with a strongly developed spiniform seta, (4) pereopod 1 with a reduced coxal process and with anterior margin of basis armed with a strongly developed, acute, spiniform seta, (5) pereopod 2 with basis having well-developed acute spine on mid anterior margin (6) ischium of pereopods 2 to 6 having anterior margin armed with one, occasional two, well-developed narrow, acute spines, (7) pereopod 4 with dactylus, not greatly reduced, but having some adjacent setae of equal or slightly greater length. The new genus is further characterized by the presence of distinctive, blunt-tipped, crenulate, spiniform setae on the carpus and propodus of pereopods 4 to 6; similar to those reported for some species of the apseudid subgenus Bunakenia (Extensibasella) . A key for the separation of the parapseudid genera within the Tribe Parapseudini that lack a distinct transverse row of setae on the first abdominal segment is presented. Akanthoparapseudes appears to share several synapomorphies with some species of the apseudid genus Bunakenia, suggesting the possibility that these two genera may represent transitional links between the families Apseudidae and Parapseudidae. Several other important overlapping characters that appear to erode the basic differences between the two families are discussed.